Creating a Digital Trauma Informed Space: Chat and Text Advocacy for Survivors of Violence. Issue 19 (October 2022) - Wood, Leila; Hairston, Dixie; Schrag, Rachel Voth; Clark, Erin; Parra-Cardona, Ruben; Temple, Jeff R.
There is little research on virtual service models like chat and text services in agencies that work with survivors of intimate partner violence (IPV) and sexual assault (SA). This study fills a gap in the research by exploring how chat and text services are provided in one IPV and SA-focused community organization. We analyzed chat and text transcripts ( n = 392) from a large multiservice, multivictimization focused agency, and conducted interviews with 11 advocates providing chat and text services through the agency hotline. Staff interviews were analyzed using grounded theory and transcripts were analyzed using content analysis. Results indicate chat/text services provide a space for connection, resource provision, education, and access to resource gain in a timely, concise, and survivor-centered way. The five major goals for chat/text advocacy models include the following: (1) rapid access to support and connection; (2) identification of options and needs for each service user; (3) increased access to resources and supports; (4) expanded understanding of violence, abuse, and harm; and (5) improvement of survivor safety. The research team identified 15 general advocacy skills and 4 chat and text specific skills used by chat/text advocates to reach program goals. Findings highlight the utility of chat/text services for increasing access to support services for survivors of violence, particularly adolescents, emerging adults, those living with an abusive individual, and during times of emergency. Future research should continue to explore the promising practice modality of chat/text services for providing advocacy to underserved and hard-to-reach populations.